AESTHETIC CHINESE PAINTING TECHNIQUE BY ARTISTS LEE MAN FONG - Gani, Sangid Zaini (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
Chinese painting is an artistic entity with its own rules and arguments that make its paintingsunique and distinctive. This article is specifically about the Chinese painting of Lee Man Fong.His background is that of an artist living and working in the Chinese diaspora in Indonesia, whoused to be a trusted assistant to President Sukarno in selecting artworks for the State Palace. Thisproblem attempts to explain the aesthetic aspect of understanding traditional Chinese painting,which deviates from the principles of ancient Chinese painting. Applying a descriptive analysismethod with an aesthetic approach aims to decipher the meaning contained in Lee Man Fong’swork, which shows a tendency toward Chinese painting, such as the presence of objects likebirds, fish, and female figures against the background of elements of Taoist and Confucianbeliefs in his works. unconsciously with the principles of the canon of Chinese art realised in theXieyi style, one of the trends in Chinese painting.Keyword: Lee Man Fong, Xieyi, Chinese Painting